The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1596/34150
|View full text |Cite
|
Sign up to set email alerts
|

Achieving World-Class Education in Adverse Socioeconomic Conditions

Abstract: This report presents the case of the municipality of Sobral in the state of Ceará, Brazil. This municipality overcame adverse socioeconomic conditions and now has the best primary and lower secondary education system in Brazil. Sobral is home to 200,000 inhabitants and in 2005 was ranked 1,366 in the national index that measures quality of education in Brazil. Twelve years later, it was ranked first among the 5,570 municipalities in both primary and lower secondary education rankings. Public education in Sobra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…A key driver of Sobral's learning gains was the clear delegation of explicit learning goals by Sobral's mayor (Loureiro and Cruz, 2020;Crouch, 2020) and subsequent collective commitment to the goals (McNaught and Tami, forthcoming). In 2000-2001, an independent learning assessment conducted by the municipality revealed that 40 percent of primary school students could not read (Loureiro and Cruz, 2020).…”
Section: Delegation Of Learning Goals and System Alignment For Learni...mentioning
confidence: 99%
“…A key driver of Sobral's learning gains was the clear delegation of explicit learning goals by Sobral's mayor (Loureiro and Cruz, 2020;Crouch, 2020) and subsequent collective commitment to the goals (McNaught and Tami, forthcoming). In 2000-2001, an independent learning assessment conducted by the municipality revealed that 40 percent of primary school students could not read (Loureiro and Cruz, 2020).…”
Section: Delegation Of Learning Goals and System Alignment For Learni...mentioning
confidence: 99%
“…Gomes' administration inherited an education system where many principals and teachers were hired based on political interests rather than meritocracy. One of the first reforms made by the municipal leadership in 1997 was to lay off 1,000 teachers who were hired without meeting the necessary technical requirements and to pass a law (Sobral Municipal Law 123, 1997) that defined technical criteria for hiring new teachers (Cruz and Loureiro, 2020).…”
Section: Initial Reform Period Of 1997-2000mentioning
confidence: 99%
“…Another important development that affected Sobral was the creation of FUNDEF, a federal education program which raised funds from federal, state, and municipal governments and redistributed them according to the number of student enrollment (Cruz and Loureiro, 2020). This gave an additional incentive to the municipality to increase enrolment and "between 1996 and 1999, student registration at the municipal network grew from 9,000 to 17,000" (Cruz and .…”
Section: Initial Reform Period Of 1997-2000mentioning
confidence: 99%
See 2 more Smart Citations